Antibacterial and antibiofilm features of mutSMAP-18 against Vibrio cholerae - Ishrat Jahan; Byambasuren Ganbaatar; Chul Won Lee; Sung-Heui Shin; Sungtae Yang (Heliyon, 2024)
Cholera continues to be a pointed global health issue, prominently in developing nations, where the disease's severe diarrheal symptoms pose substantial public health risks. With the escalating spread of antibiotic resistance among V. cholerae strains, alternative therapeutic approaches are imperative. Antimicrobial peptides are increasingly recognized for their potential, with research focusing on finding the most effective options. We explored the antibacterial and antibiofilm properties of analogues of sheep myeloid antimicrobial peptide-18 (SMAP-18) against V. cholerae in this investigation. Our prior research demonstrated that substituting glycine with alanine at different positions within SMAP-18 altered its structure and antimicrobial activity. Among these altered analogues, our focus was on a mutant variant (mutSMAP-18), characterized by glycine-to-alanine substitutions at positions 2, 7, and 13. Our results indicated that mutSMAP-18 exhibited heightened antimicrobial and antibiofilm activities against V. cholerae compared to SMAP-18. We conducted several mechanistic investigations to check the membrane integrity using DNA-binding dye, SYTOX Green or measuring calcein dye leakage and analyzing flow cytometry by fluorescence-activated cell sorting (FACScan). From these tests, we elucidated that SMAP-18 primarily functions intracellularly, while mutSMAP-18 targets the bacterial membrane. Additionally, scanning electron microscopy (SEM) images illustrated membrane disruption at lower concentrations for mutSMAP-18. Notably, mutSMAP-18 demonstrated significant antibiofilm properties against V. cholerae. Overall, these findings offer valuable perspectives for developing novel antibacterial therapies targeting the pathogenic V. cholerae.